Effects of a One-Hour Creative Dance Training on Mental Rotation Performance in Primary School Aged Children - Jansen, Petra; Richter, Stefanie (International Journal of Learning, Teaching and Educational Research, 2015)
The study presented here investigated the influence of onehour creative dance training on the spatial ability of mental rotation. Two groups of first and second graders solved a paper-pencil mental rotation test. Afterwards, one group received one lesson of creative dance training while the other group attended the regular physical education lesson. At the end of the short training period all children solved the mental rotation test again. The results show that the dancetraining group improved their mental rotation performance more than the physical education group. This study expands our further studies where we have shown that five weeks of creative dance training enhances mental rotation performance (Jansen, Kellner, & Rieder, 2013). Further studies have to be conducted which investigate the short-term effects of different kinds of physical activity on different cognitive functions and their relation to academic performance.